Developing A Simple Parabolic Motion Props: Steps and Their Applicability - Christa Triana Dewi; Rida SN Mahmudah (Jurnal Pendidikan Fisika dan Keilmuan (JPFK), 2023)
Physics props are a vital component in helping students understand the various concept of physics. Unfortunately, not all schools—especially rural ones—have access to these props, as they are usually expensive and come with a not-easy-to-understand manual book. This study aims to build parabolic motion props using simple, cheap, and easy-to-find materials. Teachers and students can “shoot” any small objects with these props, take necessary data, analyze them analytically and experimentally using Tracker software, and prove the parabolic motion they usually only find on chalkboards. Several tests were carried out to test the applicability of these props and show that they can be used to demonstrate the parabolic motion of small objects and determine their initial velocities with errors of 1.41%, 1.35%, and 4.2% for ejection angle of 30°, 45°, and 60°, respectively. The test results were also validated by comparing them to the gravity acceleration constant, resulting in errors ranging from 3.40 – 4.83%. These results concluded that teachers could build the same props in their classrooms to enhance students’ participation and understanding in learning parabolic motion.